The Saturation Effect of Obesity on Bone Mineral Density for Older People: The NHANES 2017–2020 - Zhang, Ya; Pu, Jian (Frontiers in Endocrinology, 2022)
Abstract Introduction: Previous studies have shown that obesity has a positive effect on bone mineral density (BMD). However, excessive obesity is harmful to health, especially in older adults. In addition, it is unclear what Body Mass Index (BMI) and waist circumference (WC) to maintain for the most beneficial BMD in older adults. Methods: Multivariate logistic regression models were used to investigate the association between BMI, WC, and femoral neck BMD using the most recent data from the 2017-2020 National Health and Nutrition Examination Survey (NHANES). Fitting smoothing curves and saturation effects analysis were also used to determine the association of nonlinear relationships between BMI, WC, and femoral neck BMD. Results: The analysis included a total of 2903 adults. We discovered that BMD, WC were positively linked with femoral neck BMD. The favorable associations of BMI and WC with femoral neck BMD were maintained in all subgroup analyses stratified by sex and race, except among Mexican Americans. Furthermore, smoothing curve fitting revealed that the link between BMI and BMD was not only a linear connection, and that there was a saturation point. The BMI saturation value in the femoral neck BMD was 24.3 (kg/m2), according to the saturation effect analysis. Conclusions: In persons over the age of 50, our research found a positive relationship between obesity and BMD, we also found a saturation value between BMI and BMD. According to this study, maintaining BMI at a moderate level (about 24.3 kg/m2) would result in an optimal balance between BMI and BMD in adults over 50 years of age.